Heart block and paragonimiasis. Issue 6 (December 1988) - Morrison, W L; Petch, M C
Abstract : Intracardiac granulomas can cause complete heart block. A case of complete heart block is reported in a patient who had had paragonimiasis 30 years before and who had radiographic evidence of calcified granulomas in the heart and lungs.